Antifungal Activities of Extracts from Selected Lebanese Wild Plants against Plant Pathogenic Fungi - Abou-Jawdah, Y.; Wardan, R.; Sobh, H.; Salameh, A. (Phytopathologia Mediterranea, 2004)
Extracts of nine plant species growing wild in Lebanon were tested for their efficacy against seven plantpathogenic fungi: Botrytis cinerea, Alternaria solani, Penicillium sp., Cladosporium sp., Fusarium oxysporum f. sp.melonis, Rhizoctonia solani and Sphaerotheca cucurbitae. Extracts of three of the plants, Origanum syriacum,Micromeria nervosa and Plumbago maritima, showed the highest levels of in vitro activity against spore germinationand mycelial growth of the fungi tested. Inula viscosa showed high activity against spore germination but onlymoderate activity against mycelial growth. The other five plant species tested Calamintha origanifolia, Micromeriajuliana, Ruta sp., Sideritis pullulans and Urginea maritima showed only moderate to low activity against thesefungi. Preventive sprays with extracts of O. syriacum, M. nervosa, P. maritima and I. viscosa, applied at concentrationsranging between 4 and 8% to squash and cucumber seedlings, gave efficient protection against gray moldcaused by B. cinerea and powdery mildew caused by S. cucurbitae. However, these extracts did not control green moldof citrus fruits caused by Penicillium sp. Thin layer chromatography revealed three inhibitory bands in extracts of O.syriacum, two in I. viscosa and only one in each of the other plants tested: M. nervosa, P. maritima, C. origanifoliaand Ruta sp.